2021
DOI: 10.1111/1750-3841.15760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a prebiotic and natural sweeteners on the sensory profile of skyr yogurt with mango pulp

Abstract: Skyr yogurts have been gaining prominence because of their different sensory characteristics. Due to their healthy appeal, the use of natural sweeteners to replace sucrose in this type of yogurt can be an alternative for incorporating a sweet taste, in addition to increasing the functionality of the product through the incorporation of prebiotics. This study aimed to determine whether the addition of fructooligosaccharide (FOS), sucrose, stevia, and thaumatin affects the sensory profile of the skyr yogurt with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The main characteristics of concentrated yogurts are their creamy texture and high protein content, which boosted sales of this type of yogurt, especially among consumers concerned about health and a diet rich in protein. This category in Brazil is mainly represented by Greek yogurt, which makes it better known, but interest in skyr yogurt has been increasing [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of concentrated yogurts are their creamy texture and high protein content, which boosted sales of this type of yogurt, especially among consumers concerned about health and a diet rich in protein. This category in Brazil is mainly represented by Greek yogurt, which makes it better known, but interest in skyr yogurt has been increasing [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, consumer preference expectations for skyr yogurt labels containing sweeteners were higher than for those with sucrose. However, sensory tests with skyr yogurt formulations sweetened with stevia, thaumatin, and sucrose revealed that formulations sweetened with the natural sweetener stevia were less preferred compared to yogurts sweetened with sucrose [ 9 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many scientists have incorporated probiotic and plant‐derived prebiotics into dairy products, especially in yogurt (Aliza Sigdel et al., 2018 ; Azizkhani & Tooryan, 2016 ; Fathy et al., 2022 ; Fazilah et al., 2018 ; Hashemi & Hosseini, 2021 ; Khalid et al., 2022 ; Pereira et al., 2021 ; Ranadheera et al., 2012 ; Sánchez‐Vega, 2013 ; Sohrabpour et al., 2021 ; Turgut & Cakmakci, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scientists have incorporated probiotic and plant-derived prebiotics into dairy products, especially in yogurt (Aliza Sigdel et al, 2018;Azizkhani & Tooryan, 2016;Fathy et al, 2022;Fazilah et al, 2018;Hashemi & Hosseini, 2021;Khalid et al, 2022;Pereira et al, 2021;Ranadheera et al, 2012;Sánchez-Vega, 2013;Sohrabpour et al, 2021;Turgut & Cakmakci, 2018). Shallots, for example, added to a variety of foods such as salads, pickles, and different sauces (Harris et al, 2001) are also added to yogurt in some eastern countries.…”
mentioning
confidence: 99%
“…In order to verify whether cultural diversification could interfere with the sensory profile and acceptance of formulated yogurts, sensory analyzes were conducted in two Campus). These cities were selected based on availability and differences in relation to consumption, climate, and socioeconomic and cultural aspects (Pereira et al, 2021). 240 consumers participated in the tests (120 in each city) aged between 18 and 60 years, 65%…”
Section: Sensory Analysismentioning
confidence: 99%